Nilai Perusahaan dari Sudut Corporate Social Responsibility (CSR) dan Struktur Kepemilikan Dengan Dukungan Profitabilitas - Valencia Angelica; Nera Marinda Machdar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Businesses are evaluated based on various criteria, including managerial ownership, institutional ownership and social responsibility. One of the fundamental goals of a business is to increase its value. An investor's assessment of a company's success is known as its value, which many attribute to its current stock price. The purpose of this study is to ascertain and examine how corporate social responsibility, managerial ownership, and institutional ownership affect firm value. This study will look at profitability being a moderating factor that can enhance the relationship between these variables and firm value. This research method utilizes quantitative data and causal associative research. All banking companies available on the IDX between 2019-2023 as the subject of this study. With predetermined requirements, using purposive sampling techniques. Multiple regression analysis and moderation regression analysis are the approaches used to conduct the analysis. The study results show that corporate social responsibility and ownership structure have a positive effect on firm value and profitability strengthens the effect of corporate social responsibility and ownership structure on firm value. According to this study, organizations should prioritize institutional ownership, management ownership, and corporate social responsibility as these are able to influence stock prices and increase firm value.